Analysis of Spatiotemporal Evolution and Driving Mechanism of Industrial Wastewater Discharge in China - Wu, Ya; Zhang, Li (Transactions on Economics, Business and Management Research, 2024)
This paper uses exploratory spatial data analysis (ESDA), logarithmic mean Dirichlet index ( LMDI ) and Tapio decoupling elasticity coefficient method to study the spatiotemporal evolution characteristics, main driving factors and decoupling status of industrial wastewater discharge in China from 2004 to 2019. The results show that: First, Second, economic development is the main driving factor for promoting industrial wastewater discharge; wastewater discharge intensity is the key factor in inhibiting industrial wastewater discharge; industrial structure plays an increasingly important role in wastewater reduction; the impact of population size is not significant.